The psychological experience of integrating content and language - Talbot, Kyle R. 1988-; Gruber, Marie-Theres 1987-; Nishida, Rieko 1972- (Multilingual Matters, 2021)
This book explores the psychology of teaching and learning a subject through a second or other language. It highlights the challenges and benefits of teaching and learning in integrated content and language settings and covers themes such as identity, self-concept, cognition, beliefs, well-being, interventions and professional development
Keywords: Bilingualism & multilingualism; LANGUAGE TEACHING & LEARNING (OTHER THAN ELT); The self, ego, identity, personality; LANGUAGE ARTS & DISCIPLINES / Study & Teaching; English language -- Study and teaching -- Foreign speakers; Language and languages -- Study and teaching -- Foreign speakers; Language and languages -- Study and teaching -- Psychological aspects; Language arts -- Correlation with content subjects; Content and language integrated learning; Universität; Fremdsprachenlernen; Aufsatzsammlung